Optimizing Care for Complex Biliary Patients through Team Development and Multidisciplinary Collaboration - Reiland, Allison; Stiff, Kristine; Riaz, Ahsun; Husnain, Ali (Digestive Disease Interventions, 2025)
There has been a rise in complex gallbladder and biliary procedures performed in interventional radiology (IR) at the Northwestern Memorial Hospital (NMH) with the introduction of new equipment and techniques. These procedures often call for thoughtful decision-making and multidisciplinary collaboration. The integration of various healthcare disciplines—including transplant surgery, hepatology, gastroenterology, IR, and nursing—is vital to cutting-edge innovations and improved patient outcomes. Due to the large volume of cases that can be seen, particularly at academic institutions, obstacles exist to management, chief among them being poor clinical follow-up. Thus, a dedicated IR hepatopancreaticobiliary (HPB) clinic and service line has been instated with the goal of improved clinical practice and patient management. The aim of this article is to analyze the role of multidisciplinary collaboration, discuss the rationale of a dedicated HPB service line as well as describe the structure and activities of the HPB clinic with the goal of improving the management of biliary and gallbladder patients.
Keywords: complex biliary disease; multidisciplinary collaboration; hepatobiliary; quality improvement; interventional radiology